The Influence of Salt Concentration on Wader Fish Fermentation (Rasbora lateristriata) - Ahillah, Nurul; Rusdanillah, Aoda; Afiana, Windi; sulistiani, reni; lestari, Rita puspa (Bioedukasi: Jurnal Pendidikan Biologi, 2017)
Wader fish is one of the abundant fishery products. Fermentation is one way that can be used to produce processed Wader fish. The aimed of this research  was to know the best salt concentration for fermentation of Wader fish. The research was conducted during May 2017. There are three treatment variations on salt concentration which is 25 gr / 50 ml, 30 gr / 50 ml, and 35 g / 50 ml. The results measured include pH, temperature, microbial test, acid test, and organoleptic.  pH and temperature measurements performed daily. The data obtained were analyzed and described for each treatment. The results showed that the best salt concentration on Wader fish fermentation was 30gr / 50 ml with temperature value 300C, average pH 6-9, with the amount of the highest microbes in 5.1 x 106 CFU/ml,  total organic acid content 1.16%, and with organoleptic test with highest score compared with the other two treatments.